Predicting school students' physical activity intentions in leisure-time and school recess contexts: Testing an integrated model based on self-determination theory and theory of planned behavior. - Heidi Pasi; Taru Lintunen; Esko Leskinen; Martin S Hagger (PLoS ONE)
Background Identifying psychological correlates of children's physical activity intentions may signpost potentially modifiable targets for interventions aimed at promoting physical activity participation. School recess and leisure-time outside of school are appropriate contexts in which such interventions may be delivered. However, few studies have identified correlates of physical activity intentions in these environments. Examining correlates in these contexts may provide formative evidence on which to base interventions to promote physical activity. Purpose The current study adopted an integrated theoretical model to test relations between motivational constructs from self-determination theory, social cognition constructs from the theory of planned behavior, and physical activity intentions in leisure-time and school recess contexts. Methods Finnish school children (N = 845, M age = 13.93, SD = 0.99) from three lower-secondary schools completed self-report measures of perceived autonomy support by peers, autonomous and controlled motivation, attitudes, subjective norms, perceived behavioral control, and physical activity intentions for both contexts. Results Well-fitting structural equation models controlling for past behavior indicated that autonomous motivation in the school recess context and attitude in both contexts were the most pervasive predictors of physical activity intentions, and mediated the relationship between perceived autonomy support and intentions. Multi-group analyses supported invariance of the models in both contexts across gender, grades, and school, with few variations. Conclusions The current study supports relations between motivational and social cognition correlates of children's physical activity intentions in school recess and leisure-time contexts. Future research should extend these findings to the prediction of follow-up participation in physical activity.